PENILAIAN POSTUR KERJA DAN KELELAHAN OPERATOR STORE PT XYZ MENGGUNAKAN METODE REBA: PENILAIAN POSTUR KERJA DAN KELELAHAN OPERATOR STORE PT XYZ MENGGUNAKAN METODE REBA - Kusuma, Budhi Santri; Hasibuan, Rizki Prakasa; Badruszaman, Anwar (Jurnal Teknik Ibnu Sina (JT-IBSI), 2023)
There are still many work activities that are done manually and require a person to have more abilities in bones and muscles. but one's ability is also limited, as a result when doing manual work, it is not uncommon for complaints to occur in the muscles, namely Musculoskeletal Disorders (MSDs). the activities carried out at PT XYZ are still manual, especially in the process before and after mixing the resin material, so there are many complaints in this activity. This study aims to determine the subjective complaints of MSDs, the level of ergonomics risk and the correlation between work posture, age, body mass index, smoking habits on MSDs complaints. The instruments used are NBM questionnaires, pictures of work postures and questionnaires on worker characteristics. in the NBM questionnaire, the subjective complaint most felt was in the waist with a score of 40 (100%). The method used is the REBA method with the calculation results having a high level of risk, namely in the section before the resin material mixing process an average of 11 and in the section after the resin material mixing process an average score of 9.3. based on the results of research tests related to MSDs complaints are work posture, age and body mass index, with a significance value <0.05, while those that are not related to MSDs complaints are smoking, with a significance value > 0.05.